ADRB2 gene polymorphism and emphysema heterogeneity can modulate bronchodilator response in patients with emphysema. (February 2018) - Nojiri, Masafumi; Mizuno, Shiro; Nishiki, Kazuaki; Kato, Ryo; Nakagawa, Ken; Oikawa, Taku; Iguchi, Masaharu; Osanai, Kazuhiro; Ishizaki, Takeshi; Toga, Hirohisa
Abstract: Background: Genetic variation in the β2 -adrenergic receptor ( ADRB2 ) gene has been thought to have an important role in the differential response to β2 -agonist therapy for asthma. However, previous studies have shown little evidence for an association between these ADRB2 variants and the bronchial dilator response (BDR) in chronic obstructive pulmonary disease (COPD) patients. This discrepancy could be explained by differences in the distribution and heterogeneity of pulmonary emphysema in COPD patients, since emphysema distribution and heterogeneity are thought to have a role in pulmonary function in COPD patients. We hypothesized that differences in emphysema distribution and heterogeneity may have masked significant alterations of the bronchodilator response among ADRB2 genotypes in COPD patients in previous studies. Methods: The BDR (induced by 20 μg of procaterol) was measured in 211 patients who had a smoking history of more than 10 pack/years and had undergone chest high resolution computed tomography examination. A low attenuations area (<960 Hounsfield Units) was identified and the emphysema heterogeneity index (EHI%) was calculated with a range in value from −100% to 100%. ADRB2 Arg16Gly genotyping was performed using polymerase chain reaction-restriction fragment length polymorphism analysis. Results: The BDR was augmented in patients with homogenous emphysema compared with those with upper-dominant emphysema. In patients carrying the AA genotype of ADRB2, the BDR was significantly increased in patients with upper-dominant emphysema, but not in patients with lower-dominant emphysema. Conclusion: Combination analysis of ADRB2 Arg16Gly polymorphism and EHI% may predict the effectiveness of β2 -adrenergic receptor agonist treatment in patients with COPD and emphysema.